Comparison of PLANE Technique versus Standard Echocardiography Guidance for Pediatric Pericardiocentesis - Clark, Stephen T.; Alten, Jeffrey A.; Borasino, Santiago; Hock, Kristal M.; Law, Mark A. (Journal of Pediatric Intensive Care, 2021)
Percutaneous pericardiocentesis remains a challenging and potentially dangerous procedure, particularly in small, critically ill patients. We present outcomes of the PLANE (pericardiocentesis using long-axis in-plane real-time echocardiography) technique for pediatric pericardiocentesis compared with a standard echocardiography (ECHO) guidance cohort. This was a retrospective chart review of all children undergoing percutaneous pericardiocentesis from March 2013 to February 2021 at a single center. A total of 78 procedures were performed, 52 utilizing PLANE technique and 26 utilizing standard ECHO-guidance technique. There was 100% technical success rate with only one minor complication for the entire cohort. Procedures were evenly split between the bedside intensive care unit and cardiac catheterization laboratory. PLANE technique was utilized in significantly younger (1.4 vs. 8.4 years, p = 0.008) and smaller (11.1 vs. 31.8 kg, p = 0.007) patients, as well as in most patients deemed high risk (postoperative < 7 days, extracorporeal membrane oxygenation (ECMO) support, and/or weight less than 5 kg; 19/22, p = 0.021). Other patient characteristics were similar between the two groups. There was a trend toward PLANE technique utilization by noncardiology trained operators. The PLANE technique for pediatric pericardiocentesis is safe and effective and can be effectively utilized in small and high-risk patient populations. The technical similarity to other long-axis ultrasound-guided procedures may facilitate adoption and mastery by critical care trained operators.
Keywords: pericardiocentesis; pediatric; intensive care; ultrasound